Self-Concept Dimension and Locus of Control Dimension on Employee Performance - Hakim Talaohu, Rahman; Zacharias , Tehubijuluw; Selanno , Hendry (Green Publisher Indonesia, 2024)
This research aims to analyze the influence of the self-concept dimension and the locus of control dimension on the performance of Maluku Province Regional Revenue Agency employees. This research uses a descriptive-quantitative approach with a correlational cause-effect type. The population used in this research was all 160 employees of the Maluku Province Bapenda. Determining the sample size uses Issac and Michael's sample table, where if the population is 160 people, then at the 95% confidence level, the sample is 110 people, which is determined using simple random sampling. Data analysis is multiple linear regression. The results of the research conclude that (1) Self-efficacy has a positive and significant effect on the performance of Maluku Province Bapenda employees, (2) Self-esteem has a positive and significant effect on the performance of Maluku Province Bapenda employees, (3) Self-leadership has a positive and significant effect on the performance of Provincial Bapenda employees Maluku, (4) Internal Locus of Control has a positive and significant effect on the performance of Maluku Province Bapenda employees and (5) External Locus of Control has a positive and significant effect on the performance of Maluku Province Bapenda employees.